2014
DOI: 10.1016/j.juro.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Emergency Department Imaging Practices for Pediatric Urolithiasis: Room for Improvement

Abstract: Purpose Children are particularly vulnerable to the harmful effects of medical radiation, and children with urolithiasis are one group who may receive repeated radiation-intensive imaging tests. Our study aimed to characterize imaging practices for children presenting to the emergency department (ED) with suspected urolithiasis (SU) and determine factors associated with the choice of imaging study. Methods Using the 2006-10 Nationwide Emergency Department Sample (NEDS), we conducted a retrospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…A more recent paper has shown that up to 87% of paediatric emergency admissions with suspected urolithiasis were imaged with CT [12]. Yet the same authors recommend an increased use of ultrasound to avoid the radiation exposure and potential cancer risk encountered as a result of CT scanning [12]. In our patient group only 18% of patients were subjected to a CT scan with the majority of these being performed initially in other units prior to referral to our tertiary centre.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A more recent paper has shown that up to 87% of paediatric emergency admissions with suspected urolithiasis were imaged with CT [12]. Yet the same authors recommend an increased use of ultrasound to avoid the radiation exposure and potential cancer risk encountered as a result of CT scanning [12]. In our patient group only 18% of patients were subjected to a CT scan with the majority of these being performed initially in other units prior to referral to our tertiary centre.…”
Section: Discussionmentioning
confidence: 98%
“…However, despite this recommendation a recent US paper has shown an increase in the use of CT scanning from 26% in 1999 to 45% in 2008 when imaging children with urolithiasis [9]. A more recent paper has shown that up to 87% of paediatric emergency admissions with suspected urolithiasis were imaged with CT [12]. Yet the same authors recommend an increased use of ultrasound to avoid the radiation exposure and potential cancer risk encountered as a result of CT scanning [12].…”
Section: Discussionmentioning
confidence: 99%
“…Kritisch betrachtet hat die hohe Sensitivität und Spezifität der NCCT zu einer deutlichen Zunahme der CT-Untersuchungen bei Kindern geführt, so dass in den USA die CT bei Kindern mittlerweile die häu-figste Primärdiagnostik bei Verdacht auf eine Urolithiasis ist. Besorgniserregend aus europäischer Sicht ist, dass rund 87% der Patienten keine vorherige Sonographie erhielten [18]. Die Gefährlichkeit dieses Trends konnte eine australische Groß-felduntersuchung mit einer Kohorte von 680.000 Patienten, die alle im Kindesalter eine CT erhielten, zeigen: die Karzinominzidenz war um 24% erhöht und steigerte sich bei repetitiven Untersuchungen auf >50% [25].…”
Section: Pädiatrische Urolithiasisunclassified
“…5 Likewise, the Nationwide Emergency Department Sample and the State Emergency Department Databases are available as part of the Healthcare Cost and Utilization Project and have been used for analyses of imaging practices. 45,73 In addition, the Dose Index Registry is a relatively new registry from the American College of Radiology-sponsored National Radiology Data Registry (www.nrdr.acr.org) and collects anonymized data from CT studies completed at participating institutions in the United States. 74 Data continue to emerge from this resource and a recent study characterized radiation dose indexes for renal colic protocol CTs performed in the United States.…”
Section: Introductionmentioning
confidence: 99%